Synthesis, characterization and neurotoxicity screening of schiff base ligands derived from 1,8-Diaminonaphthalene and their Cu(ii), Co(ii), Ni(ii) and Zn(ii) complexes / Ahmad Fauzi Abu Bakar - Abu Bakar, Ahmad Fauzi (2013)
Five Schiff base ligands were successful synthesized from 1,8-diaminonaphthalene with 2-hydroacetophenone, 5-bromo-2-hydroxyacetophenone, salicyldehyde, 2-4,dihydroxybenayldehyde and 3-hydroxy-4-methoxybenzaldehyde in the ratio 1:2. Twenty complexes of Cu(II), Co(II), Ni(II) and Zn(II) with the five ligands were obtained with 1:1 ratio of ligand:metal. The chemical structures were investigated and elucidated using elemental analysis (C,H,N), infrared spectroscopy, 1 H and 13C nuclear magnetic resonance spectroscopy, ultraviolet-visible spectroscopy, melting point measurement and magnetic susceptibility measurement. The paramagnetic Cu(II) and Co(II) complexes were observed to display v(C=N) band in the range 1601 to 1638 cm'1, while those of the diamagnetic Ni(II) and Zn(II) complexes displayed v(C=N) band in the region 1587 to 1638 cm'1. From the effective magnetic moment (|^eff) values, it was indicate that the nickel(II) complexes adopted square planar geometry while all the cobalt(II) complexes were tetrahedral. The representative compounds of CoLl and LI showed UV-Vis absorption bands at 260 to 332 nm assignable to n—>n* transition of the aromatic systems. The band at 298 nm for ligand was likely due to n—>n* and tt— electron transitions of the conjugated C=C chromophore of the naphthalene and phenyl moieties. Absorption for cobalt(II) complex showed a bathocromical shift to the free ligand, caused by the coordination of metal to the ligand, in agreement with the IR spectral results. The neurotoxicity screening on treated human neuroblastoma SH-SY5Y cell lines revealed that the compound were not toxic to the cell line.